A Review of the Russian translation of Maciej Górny, Wielka wojna profesorów. Nauki o człowieku (1912–1923). Warsaw: Instytut Historii PAN , 2014, 284 pp. (Антропологический форум / Forum for Anthropology and Culture, 2023)
The text is a review of Maciej Górny’s Wielka wojna profesorów. It gives an overview of the main propositions of Górny’s work, and raises the question of how far scientific knowledge is influenced by the unscientific (nationalist, political, ideological) foundations of scholars’ thought, and whether that influence can be eradicated. Both Górny’s book and current events lead the author to melancholy conclusions.